Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1080/13537113.2010.490757
|View full text |Cite
|
Sign up to set email alerts
|

Legislating Separation and Solidarity in Plural Societies: The Chinese in Indonesia and Malaysia

Abstract: The Chinese minority plays a dominant role in the economies of Indonesia and Malaysia, a fact that evokes indigenous resentment. However, Indonesia and Malaysia dealt differently with the issue. Malaysia legislated the Malays into the economy and protected Chinese citizenship, making them an integral part of a multicultural state. By contrast, New Order Indonesia adopted policies of economic manipulation, forced assimilation, and unequal citizenship. Only when the New Order regime fell did Chinese integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Compared to North American cohorts where the MoCA was developed, the Malaysian HIV population is typically younger, includes people with a wider range of educational achievement, and includes an ethnic diversity where persons of Chinese background tend to have more socioeconomic opportunities than their Malay and Indian counterparts [20, 21]. Therefore, it is important to account for this complex demographic diversity when utilizing screening tools because such factors are known to affect normal cognitive performance and thus impact the accuracy of cognitive impairment detection in clinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to North American cohorts where the MoCA was developed, the Malaysian HIV population is typically younger, includes people with a wider range of educational achievement, and includes an ethnic diversity where persons of Chinese background tend to have more socioeconomic opportunities than their Malay and Indian counterparts [20, 21]. Therefore, it is important to account for this complex demographic diversity when utilizing screening tools because such factors are known to affect normal cognitive performance and thus impact the accuracy of cognitive impairment detection in clinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…The situation is like the bloom of many flowers (Coppel, 2003). Periodically, Indonesian government has made revision on discriminative acts and regulations related to Indonesian-Chinese (Jacobsen, 2005;Suryadinata, 2007;Sukma, 2009;Hwang &Sadiq, 2010;Tan, 2011;Jiaxuan, 2011;Suryadinata,2012;Liji, 2012;Mahfud, 2013). The third Indonesian president B.J.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a dearth of empirical research that has examined aspects of social solidarity in one ethnic group by drawing on a comparison of majority and minority communities, such as that by Hwang and Sadiq (2010): there are comparisons across nation states (see for example, Sangiovanni, 2013). Much of the research conducted concentrates on aspects of social solidarity either within majority populations (Chan and Chan, 2008;Cheung and Ma, 2011), or minority populations in the context of the host community (Schuster and Solomos, 2004) With this backdrop, the overall research aim was to undertake a comparative study that would lead to a better understanding of the nature of social solidarity in two Chinese populations , one a majority community in Hong Kong, the other a minority community in the UK.…”
Section: Research Aimsmentioning
confidence: 99%
“…A modest number of such studies have explored aspects of social solidarity in locations where Chinese is a minority ethnic culture. Hwang and Sadiq (2010) have compared the influence of social solidarity on economic social and political integration of the Chinese minority in Malaysia and Indonesia. In the UK, Chan et al (2007a) have demonstrated that social solidarity among UK Chinese has been weakened by their competitive approach to business in the catering trade.…”
mentioning
confidence: 99%